2019
DOI: 10.4103/ijd.ijd_458_18
|View full text |Cite
|
Sign up to set email alerts
|

The association between attention-deficit/hyperactivity disorder and Atopic dermatitis: A study among Iranian children

Abstract: Background:The co-occurrence of attention-deficit/hyperactivity disorder (ADHD) with atopic dermatitis (AD) has been well described in some recent association studies; however, we did not have any perspective on this relationship in our country.Aim and Objective:Hence, the present study aimed to assess the prevalence of ADHD in children with AD.Materials and Methods:This cross-sectional study was performed on 95 consecutive children and adolescents (aged 4–18 years) who were referred to dermatology clinics at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Several previous studies did not find significant association between allergic disorders and the development of ADHD 15,17 or ASD, 25,31 . However, most studies that were done in different parts of the world provide evidence for high risk of pediatric allergic patients to develop ADHD 17,24,30,[32][33][34] or ASD 14,17,23,30,34 regardless to the ethnicity of the enrolled patients. A meta-analysis by Schans et al, 26 reported that asthma, rhinitis, and eczema were independent risk factors for ADHD development which is similar to our observation.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies did not find significant association between allergic disorders and the development of ADHD 15,17 or ASD, 25,31 . However, most studies that were done in different parts of the world provide evidence for high risk of pediatric allergic patients to develop ADHD 17,24,30,[32][33][34] or ASD 14,17,23,30,34 regardless to the ethnicity of the enrolled patients. A meta-analysis by Schans et al, 26 reported that asthma, rhinitis, and eczema were independent risk factors for ADHD development which is similar to our observation.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies investigated the association of a single allergic disorder, [15][16][17][29][30][31][32][33] or up to three allergic comorbidities, 14,23,24,26,28,34,35 and ADHD/ASD. To the best of our knowledge, the present study is the first study which enrolled children with up to six allergic comorbidities (Table 1) including drug allergy that was not previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the present study is the first study which enrolled children with up to six allergic comorbidities (Table 1) including drug allergy that was not previously studied. Moreover, whereas most previous studies reported the association between allergic disorders and ADHD or ASD, 15,16,29,31 we investigated the link to ADHD and ASD (or both ADHD+ASD) using our large pediatric cohort, with the same methodological and statistical analysis that add to the validity of our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADHD is the most common neuropsychiatric comorbidity in children with AD [62,63]. A combination of neurological control and treatment of AD symptoms could provide better therapeutic outcomes in these AD patients.…”
Section: Discussionmentioning
confidence: 99%